2022
DOI: 10.3340/jkns.2021.0200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hub Genes in the Pathogenesis of Ischemic Stroke Based on Bioinformatics Analysis

Abstract: Objective : The present study aimed to identify the function of ischemic stroke (IS) patients’ peripheral blood and its role in IS, explore the pathogenesis, and provide direction for clinical research progress by comprehensive bioinformatics analysis.Methods : Two datasets, including GSE58294 and GSE22255, were downloaded from Gene Expression Omnibus database. GEO2R was utilized to obtain differentially expressed genes (DEGs). Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“… 41 , 42 ZC3H12A is induced by cholesterol and is involved in cholesterol-induced HUVEC DNA damage that exacerbates atherosclerotic plaque formation; 43 , 44 Whereas studies have shown that upregulation of ZC3H12A expression has a mitigating effect on ischemic stroke, 45 however, the mechanism of ZC3H12A’s role in atherosclerosis and ischemic stroke needs further investigation. Previous Bioinformatics Analysis Shows Elevated KRAS in Ischemic Stroke, 46 and can promote atherosclerotic plaque formation. 47 The mechanism of KRAS in ischemic stroke and atherosclerosis is not clear.…”
Section: Discussionmentioning
confidence: 99%
“… 41 , 42 ZC3H12A is induced by cholesterol and is involved in cholesterol-induced HUVEC DNA damage that exacerbates atherosclerotic plaque formation; 43 , 44 Whereas studies have shown that upregulation of ZC3H12A expression has a mitigating effect on ischemic stroke, 45 however, the mechanism of ZC3H12A’s role in atherosclerosis and ischemic stroke needs further investigation. Previous Bioinformatics Analysis Shows Elevated KRAS in Ischemic Stroke, 46 and can promote atherosclerotic plaque formation. 47 The mechanism of KRAS in ischemic stroke and atherosclerosis is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Hsa-miR-181a-5p is associated with inflammation, upregulated in response to TGFβ signaling [52], and has been identified as a critical regulatory miRNA in ischemic strokes [53]. Serum levels of the protein encoded by its gene targets ATG5 is presented as a biomarker for AIS patients [54], while another gene target, ATM is involved in neuroprotection in the initiation of protective mechanisms in ischemic preconditioning but promotes neuronal cell death following the ischemic insult [55].…”
Section: Discussionmentioning
confidence: 99%